The Effect of Current Ratio, Debt to Equity Ratio, Return On Assets, and Net Profit Margin on Profit Growth - Anny Widiasmara; Agiesti Kusherawati; Retno Cahyaningati; Ratna Wijayanti Daniar Paramita (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2022)
This study aims to empirically test the effect of the Current Ratio, Debt to Equity Ratio, Return On Assets, and Net Profit Margin on Profit Growth. The population used is the consumer goods sector companies listed on the IDX in 2016-2020. Sample selection using purposive sampling method. The type of data used is secondary data from the 2016-2020 annual report. The hypothesis was tested using descriptive statistical analysis, classical assumption test, multiple linear regression, hypothesis testing and coefficient of determination test using SPSS 23. The results showed that Debt to Equity Ratio and Net Profit Margin had a significant effect on Profit Growth, Current Ratio and Return On Assets did not significant effect on Profit Growth.